Biomaterial-based strategies: a new era in spinal cord injury treatment - Shihong Zhu; Sijun Diao; Xiaoyin Liu; Zhujun Zhang; Fujun Liu; Wei Chen; Xiyue Lu; Huiyang Luo; Xu Cheng; Qiang Liao; Zhongyu Li; Jing Chen (Neural Regeneration Research)
Enhancing neurological recovery and improving the prognosis of spinal cord injury have gained research attention recently. Spinal cord injury is associated with a complex molecular and cellular microenvironment. This complexity has prompted researchers to elucidate the underlying pathophysiological mechanisms and changes and to identify effective treatment strategies. Traditional approaches for spinal cord injury repair include surgery, oral or intravenous medications, and administration of neurotrophic factors; however, the efficacy of these approaches remains inconclusive, and serious adverse reactions continue to be a concern. With advancements in tissue engineering and regenerative medicine, emerging strategies for spinal cord injury repair now involve nanoparticle-based nanodelivery systems, scaffolds, and functional recovery techniques that incorporate biomaterials, bioengineering, stem cell, and growth factors as well as three-dimensional bioprinting. Ideal biomaterial scaffolds should not only provide structural support for neuron migration, adhesion, proliferation, and differentiation but also mimic the mechanical properties of natural spinal cord tissue. Additionally, these scaffolds should facilitate axon growth and neurogenesis by offering adjustable topography and a range of physical and biochemical cues. The three-dimensionally interconnected porous structure and appropriate physicochemical properties enabled by three-dimensional biomimetic printing technology can maximize the potential of biomaterials used for treating spinal cord injury. Therefore, correct selection and application of scaffolds, coupled with successful clinical translation, represent promising clinical objectives to enhance the treatment efficacy for and prognosis of spinal cord injury. This review elucidates the key mechanisms underlying the occurrence of spinal cord injury and regeneration post-injury, including neuroinflammation, oxidative stress, axon regeneration, and angiogenesis. This review also briefly discusses the critical role of nanodelivery systems used for repair and regeneration of injured spinal cord, highlighting the influence of nanoparticles and the factors that affect delivery efficiency. Finally, this review highlights tissue engineering strategies and the application of biomaterial scaffolds for the treatment of spinal cord injury. It discusses various types of scaffolds, their integrations with stem cells or growth factors, and approaches for optimization of scaffold design.